“Just Words? Just Speeches?” On the Economic Value of Charismatic Leadership - Antonakis, John; d’Adda, Giovanna; Weber, Roberto A.; Zehnder, Christian (Management Science, 2022)
Leadership theories in sociology and psychology argue that effective leaders influence follower behavior not only through the design of incentives and institutions, but also through personal abilities to persuade and motivate. Although charismatic leadership has received considerable attention in the management literature, existing research has not yet established causal evidence for an effect of leader charisma on follower performance in incentivized and economically relevant situations. We report evidence from field and laboratory experiments that investigate whether a leader’s charisma—in the form of a stylistically different motivational speech—can induce individuals to undertake personally costly but socially beneficial actions. In the field experiment, we find that workers who are given a charismatic speech increase their output by about 17% relative to workers who listen to a standard speech. This effect is statistically significant and comparable in size to the positive effect of high-powered financial incentives. We then investigate the effect of charisma in a series of laboratory experiments in which subjects are exposed to motivational speeches before playing a repeated public goods game. Our results reveal that a higher number of charismatic elements in the speech can increase public good contributions by up to 19%. However, we also find that the effectiveness of charisma varies and appears to depend on the social context in which the speech is delivered. This paper was accepted by Yan Chen, behavioral economics and decision analysis.